Recording the brain in vivo emerging technologies for the exploration of mental health conditions - Free, Tristan (BioTechniques, 2024)
Standfirst Mounting interest in mental health conditions over the last two decades has been coupled with the increasing sophistication of techniques to study the brain in vivo. [Formula: see text]